PROBLEMS OF RESERVE DEVELOPMENT PROJECTS IN COMMERCIAL BANKS - Daminova Sardorxon Baxromovna (Journals Park Publishing, 2025)
One of the ways to manage credit risk, which was left by a commercial bank on its own retention, is a reservation, the purpose of which is to compensate the bank for material damage in the event of the realization of this risk. The article presents an approach to considering reservations in commercial banks as a system consisting of three interrelated blocks: fundamental, organizational and regulatory.
Keywords: Reservation, impairment, expected credit losses, credit risk, commeeical banks.